University didactics according to the new paradigms and current needs in Peru - Jaime Cardenas, Jorge Luís (2021)
The essay shown below deals with a very general topic such as didactics in Higher Education. Its fundamental objective is aimed at analyzing its didactic principles and some elements of the university's teaching-learning process with the new paradigms that are being imposed on a global level, which in turn rely on various sources of notable theorists that have evolved as makes society. The method rested on the review and analysis of different theoretical sources of a documentary nature and their relationship with the subject, which at the same time appear in the references. In it, no rigid schemes have been drawn nor formulas are provided when dealing with specifically qualitative elements, however, some suggestions are offered that directly link the so-called Knowledge Society with the necessary didactic changes that require active ways so that the student becomes an actor and creator of his own knowledge. In this sense, emphasis has been placed on the new technological tools that have emerged precisely from the development of knowledge itself, briefly analyzing the pros and cons of this use; taking for granted that they mean a remarkable step forward as long as they are deepened into their essence and are properly applied. Although the work is aimed at the Peruvian reality, it is no less true that it also involves other countries in the area where didactic changes are a common denominator according to current social evolution.